Clinical features and treatment options for pediatric adrenal incidentalomas: a retrospective single center study - Xiaojiang Zhu; Saisai Liu; Yimin Yuan; Nannan Gu; Jintong Sha; Yunfei Guo; Yongji Deng (BMC, 2024)
Abstract Background The aim of this study was to investigate the clinical features and treatment options for pediatric adrenal incidentalomas(AIs) to guide the diagnosis and treatment of these tumors. Methods The clinical data of AI patients admitted to our hospital between December 2016 and December 2022 were collected and retrospectively analyzed. All patients were divided into neonatal and nonneonatal groups according to their age at the time of the initial consultation. Results In the neonatal group, 13 patients were observed and followed up, and the masses completely disappeared in 8 patients and were significantly reduced in size in 5 patients compared with the previous findings. Four patients ultimately underwent surgery, and the postoperative pathological diagnosis was neuroblastoma in three patients and teratoma in one patient. In the nonneonatal group, there were 18 cases of benign tumors, including 9 cases of ganglioneuroma, 2 cases of adrenocortical adenoma, 2 cases of adrenal cyst, 2 cases of teratoma, 1 case of pheochromocytoma, 1 case of nerve sheath tumor, and 1 case of adrenal hemorrhage; and 20 cases of malignant tumors, including 10 cases of neuroblastoma, 9 cases of ganglioneuroblastoma, and 1 case of adrenocortical carcinoma. Conclusions Neuroblastoma is the most common type of nonneonatal AI, and detailed laboratory investigations and imaging studies are recommended for aggressive evaluation and treatment in this population. The rate of spontaneous regression of AI is high in neonates, and close observation is feasible if the tumor is small, confined to the adrenal gland and has no distant metastasis.